The Labor Market and Economic Adjustment - Agenor, Pierre-Richard (IMF Working Papers; Working Paper ;, 1995)
This paper examines the role of the labor market in the transmission process of adjustment policies in developing countries. It begins by reviewing the recent evidence regarding the functioning of these markets. It then studies the implications of wage inertia, nominal contracts, labor market segmentation, and impediments to labor mobility for stabilization policies. The effect of labor market reforms on economic flexibility and the channels through which labor market imperfections alter the effects of structural adjustment measures are discussed next. The last part of the paper identifies a variety of issues that may require further investigation, such as the link between changes in relative wages and the distributional effects of adjustment policies.